Achilles Tendon Allograft with Semitendinosus Autograft Reinforcement Is a Successful Treatment for Chronic Patellar Tendon Rupture: Report of Two Cases - Lucie Regennass; Mathieu Boissard; Alban Fouasson-Chailloux; Ronan Guillou; Cecile Toanen; Vincent Crenn (Case Reports in Orthopedics)
Rupture of the patellar tendon must be diagnosed urgently because reconstruction of the extensor mechanism produces better results when it is performed in acute conditions. Reconstruction of chronic extensor mechanism rupture on the contrary is very challenging. Several surgical techniques have been described using a variety of graft choices and fixation methods, but the optimal approach is still under debate. We report our experience of two cases of chronic patellar tendon rupture reconstruction using an Achilles tendon allograft reinforced by a vascularized ipsilateral semitendinosus tendon frame. The rapid functional recovery of the range of motion, only three months postoperatively, showed us that this reconstruction technique was effective.